Puerperal Period Reproductive Disorde,rs in Surti Buffaloes During Different Parity - MURUGEPPA, A; DUBEY, B M (The Indian Journal of Animal Reproduction, 2023)
The overall incidence of various reproductive disorders during puerperal period were studied in 622 calvings of 292 farm born surti buffaloesfro m the herd of All India Co-ordinated Research Project on Buffaloes, Main Research Station,Un iversity of Agricultural Sciences; Dharwad. The overall incidence of retention of placenta, septic metritis, metritis, endometritis, vaginitis, Pyometra and Post-partum cervicovaginal prolapse in 622 calvings were 7.56, 8.68, 9.81. 8.36, 1.77, 7.56 and 2.40 percent respectively. The percentage incidence of all the reproductive disorders were comparatively low in the first parity followed by increasing tendency during second,third and fourth parities.